Assessment and self-assessment of the pharmacists’ competencies using the Global Competency Framework (GbCF) in Serbia - Stojkov, Svetlana; Tadić, Ivana; Crnjanski, Tatjana; Krajnović, Dušanka (Vojnosanitetski pregled, 2017)
Background/Aim. Pharmacists’ competence represents a dynamic framework of knowledge, skills and abilities to carry out tasks, and it reflects on improving the quality of life and on patients’ health. One of the documents for the Evaluation and Competency Development of Pharmacists is the Global Competency Framework (GbCF). The aim of this study was to implement the GBCF document into Serbian pharmacies, to perform assessment and self assessment of the competencies. Methods. The assessment and self-assessment of pharmacists’ competencies were performed during the period 2012−13 year in eight community pharmacy chains, in seven cities in Serbia. For assessment and self-assessment of pharmacists competencies the GbCF model was applied, which was adjusted to pharmaceutical practice and legislation in Serbia. External assessment was conducted by teams of pharmacists using the structured observation of the work of pharmacists during regular working hours. Evaluated pharmacists filled out the questionnaire about demographic indicators about the pharmacist and the pharmacy where they work. Results. A total of 123 pharmacists were evaluated. Pharmacists’ Professional Competency Cluster (KK1) had the lowest score (average value 2.98), while the cluster Management and Organizational Competency (KK2) had the highest score (average value 3.15). The competence Recognition of the Diagnosis and Patient Counseling (K8), which belonged to the cluster KK1, had the lowest score (average value for assessment and self-assessment were 2.09, and 2.34, respectively) among the all evaluated competencies. Conclusion. GbCF might be considered as an instrument for the competencies’ evaluation/self-evaluation and their improvement, accordingly.